SuFEx on the Surface: A Flexible Platform for Postpolymerization Modification of Polymer Brushes. (9th September 2015) - Yatvin, Jeremy; Brooks, Karson; Locklin, Jason
Abstract: Polymer brushes present a unique architecture for tailoring surface functionalities due to their distinctive physicochemical properties. However, the polymerization chemistries used to grow brushes place limitations on the monomers that can be grown directly from the surface. Several forms of click chemistry have previously been used to modify polymer brushes by postpolymerization modification with high efficiency, however, it is usually difficult to include the unprotected moieties in the original monomer. We present the use of a new form of click chemistry known as SuFEx (sulfur(VI) fluoride exchange), which allows a silyl ether to be rapidly and quantitatively clicked to a polymer brush grown by free‐radical polymerization containing native ‐SO2 F groups with rapid pseudo‐first‐order rates as high as 0.04 s −1 . Furthermore, we demonstrate the use of SuFEx to facilely add a variety of other chemical functional groups to brush substrates that have highly useful and orthogonal reactivity, including alkynes, thiols, and dienes.